2021
DOI: 10.1186/s12944-021-01558-x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of non-HDL-C in predicting proteinuria remission of idiopathic membranous nephropathy: a retrospective cohort study

Abstract: Background Idiopathic membranous nephropathy (IMN) may have various clinical outcomes. Hyperlipidemia is quite common in IMN. However, the utility of the lipid profile in predicting outcomes remains unknown. This study aimed to explore the correlation between hyperlipidemia and proteinuria remission in IMN. Methods 256 patients who diagnosed with IMN confirmed by renal biopsy in Wuhan Tongji Hospital from January 2016 to October 2020 were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…PLA2R has been considered the major target antigen for IMN, and anti-PLA2R is a widely accepted diagnostic and prognostic biomarker (17). Our preliminary results indicated that hypercholesterolemia at baseline is an independent risk factor for persistent proteinuria in IMN (11). Herein, we found that hypercholesterolemia at onset was correlated with glomerular and tubular lesions, glomerular PLA2R deposit, and serum anti- PLA2R titers in a large Chinese cohort.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…PLA2R has been considered the major target antigen for IMN, and anti-PLA2R is a widely accepted diagnostic and prognostic biomarker (17). Our preliminary results indicated that hypercholesterolemia at baseline is an independent risk factor for persistent proteinuria in IMN (11). Herein, we found that hypercholesterolemia at onset was correlated with glomerular and tubular lesions, glomerular PLA2R deposit, and serum anti- PLA2R titers in a large Chinese cohort.…”
Section: Discussionmentioning
confidence: 59%
“…In the present study, triglyceride (TG), total cholesterol (TC), highdensity lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and non-high-density lipoprotein cholesterol (non-HDL-C) were evaluated as lipid profiles and their roles evaluated in IMN. In a previous study, we demonstrated that hypercholesterolemia at baseline is an independent risk factor for non-remission of proteinuria in IMN patients (11). However, whether hyperlipidemia is correlated with the outcomes via any pathological parameter remains to be clarified.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Hypercholesterolemia was proven to be associated with glomerular PLA2 receptor deposition and independently predicted proteinuric outcome in patients with MN [4]. Dong et al [21] reviewed 256 patients with MN diagnosed by renal biopsy, and lipid profiling found that non-HDL levels correlated most strongly with proteinuria. In our MN model mice, except for the elevated levels of kidney and liver injury indicators in serum, the levels of lipid metabolism indicators, TC, TG, and AA metabolism indicators, including AA, PGI 2 , TXA 2 , and LTB 4 , were significantly higher, which is consistent with previous reports [22].…”
Section: Discussionmentioning
confidence: 99%